1982
DOI: 10.1002/anie.198200873
|View full text |Cite
|
Sign up to set email alerts
|

The Norbornyl Cation: Prototype of a 1,3‐Bridged Carbocation

Abstract: The protracted discussion of whether 2-norbornyl cations are bridged or unbridged, i. e. nonclassical or classical, has lost most of its meaning, because these terms apply to the extremes of a graded series of structures. This is shown by a study of the solvolysis of stereoisomeric 6-substituted 2-norbornyl toluenesulfonates. Norbornyl and other bicyclic cations, to which nucleophiles have limited access, are stabilized by bridging between the cationic center and a saturated carbon atom in the @-position. Brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 48 publications
(2 reference statements)
0
20
0
1
Order By: Relevance
“…their inductivities differ widely. It is concluded that through space induction involves graded bridging of the substituent-bearing C-atom to the incipient cationic center at C (2) and that this involves differential bridging strain. The different reactivities of unsubstituted 2-exo-and 2-endo-norbornyl derivatives can then be ascribed to a stereoelectronic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…their inductivities differ widely. It is concluded that through space induction involves graded bridging of the substituent-bearing C-atom to the incipient cationic center at C (2) and that this involves differential bridging strain. The different reactivities of unsubstituted 2-exo-and 2-endo-norbornyl derivatives can then be ascribed to a stereoelectronic effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand 2-exo-and 2-endo-norbornanols were obtained when R was an acceptor, indicating that unbridged cations 5 are attacked from both sides of C (2) [ 11 [5]. Finally, reversible Wagner-Meerwein rearrangements of the cations 3 and 4 were fast relative to their capture by solvent when R was a donor, but slow when R was an acceptor, as in 5 and 6 [6], a sign that bridging and rearrangement are related.…”
mentioning
confidence: 96%
“…The large p-value for 5 indicated an unusually strong inductive interaction between C (6) and the incipient cationic center at C (2) and led to the conclusion that induction involves graded C-participation, i.e. 1,3-bridging, as illustrated in 8 [5] [13]. On this basis bridging appears to be less favorable in the adamantyl cation 9 than in the norbornyl cation 8.…”
Section: I)mentioning
confidence: 97%
“…The rapid equilibrium in cations 495 and 496 has been frozen out in the solid state at À165 C and À160 C, respectively, by Yannoni and co-workers. The controversy [27][28][29][30][31][32][33][34][35][36][37]40,[862][863][864][865][866] about it is well known, and the question has been whether the ion has a symmetrically bridged nonclassical structure 504 with a pentacoordinate carbon atom or is a rapidly equilibrating pair of classical trivalent ions 505a and 505b. Some representative examples, namely, the bisadamantyl (499), 859 2-norbornyl (500), 40 7-perhydropentalenyl (501), 188 9-decalyl (502), 188 and pentacylopropylethyl (503) 860 cations, are given in Scheme 3.19.…”
Section: H +mentioning
confidence: 99%